On the ethical use of placebos. Issue 2 (17th February 2015) - Rawlins, Richard
Abstract Sham drugs, fake therapies and non‐effective treatments have long been used to placate patients and are often referred to as 'placebos'. Placebos are used regularly as controls for clinical drug trials but their use as therapeutic modalities in their own right is controversial. This article combines my experience as a consultant surgeon with the insight of also being a magician, and member of The Magic Circle, UK, in viewing the world of deception and delusion in health care. This perspective endorses the use of placebos within the paradigm of ethical care based on patients giving fully informed consent. This means that unless and until there is generally accepted plausible evidence that a specific complementary or alternative medicine (CAM) or practice produces outcomes better than those produced by therapeutic encounters with attentive empathic practitioners alone, it should be accepted that the CAM therapy works through the mechanism of a placebo response – and that is what patients should be told. That may diminish the beneficial effects of the CAM/placebo therapy, but the placebo response will not be entirely negated – honesty and intellectual integrity should trump the convenience of the practitioner.